TVET PROGRAMS IN NIGERIA: AN ASSESSMENT OF THE TECHNICAL SKILLS OF STUDENTS IN THE TECHNICAL COLLEGES IN RIVER STATE, NIGERIA - Okechukwu Chuks, Agbo (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
The Technical Vocational Education and Training (TVET) system is crucial in producing highly skilled labor to meet industry demands. To successfully equip students with technical skills that would enable them to meet the current work demands and professional expectations, an empirical study is required to assess the technical competence of students enrolled in TVET programs. Indeed, little is known about the technical skills of students in technical colleges. The present study evaluated students' technical skills at government technical colleges in River State, Nigeria. Two hundred fifty-five students were purposively pooled from the government technical college located in different parts of River State (Eleogu, Tombin, Ahoada, and Port Harcourt) participated in the study. They completed a questionnaire measuring technical skills in six dimensions. The result revealed a high technical competence outcome for material and application (75.5%), work planning (71%), practical knowledge (66.7%), and theoretical knowledge (59.4%). Also, the findings indicated low technical skills for equipment maintenance (15.6%) and workshop management (18.1%). The result has implications for the sustainability and development of TVET in Nigeria.